Online Learning with Project Based Learning Approach in the Human Performance Technology Course - Lasamahu, Beatriks; Siregar, Eveline; Sukardjo, Moch (LPPM Undiksha, 2021)
The development of the era and the 4.0 revolution requires universities to be able to answer challenges to face technological advances and competition in the world of work in the era of globalization. Online learning is a form of learning that can answer the times, technological advances and knowledge of learning development in universities. This study aims to design the online learning with Project Based Learning approach in the Human Performance Technology course. This study uses the R&D method in designing online learning. The online learning design is carried out using the PEDATI model. The PEDATI model itself has several design steps starting from formulating online learning, mapping material, determining asynchronous or synchronous and designing the selected learning path. Asynchronous learning at PEDATI which consists of, deepening, applying and evaluating with a project-based learning approach that has six steps. The results of the research resulted in an online learning design which consisted of formulating learning outcomes, mapping materials, making asynchronous learning flows combined with project-based learning syntax. Selection of materials, forms of discussion, assignments to evaluation forms can be arranged in such a way and combined with the LMS used. Online learning designs that are designed with the right learning activities can make learning more meaningful for students. With online learning, face-to-face learning can be a means of discussion rather than just delivering material.